Studies in symbolic interaction. Vol. 26 - Denzin, Norman K.; Bai, Ruoyun (Amsterdam ; London : JAI, 2003)
The first part of this collection of essays is devoted to the work of Peter Hall in communications and sociological inquiries. It emphasises developments in interactionist theory, as well as examples of post-modern ethnograohy and performance texts on border crossings and performances.
Description based on print version record.
Keywords: Symbolic interactionism; Communication studies; Sociology & anthropology; Social Science -- Sociology -- General